The Phenomenon Of Minimalism Trends In Contemporary Kids Wear In Indonesia: A Visual Study Of the Shift On Kids Fashion Styles And The Characteristics Of Generation Z Consumers - Wening Gilang Nawangi; Puji Rahmah Shalih; Dion Darsa Sabrian (International Journal of Health Engineering and Technology, 2026)
The minimalism trend in kids fashion style represents a minimalist aesthetic characterized by neutral and earth-tone color palettes, along with simplified forms (minimal form) in silhouettes. In Indonesia, this trend has developed under the influence of social media and the visual preferences of Generation Z as young parents who tend to favor aesthetically pleasing styles. This study focuses on analyzing the trend phenomenon and the selection of minimalist styles in contemporary kids wear in Indonesia through a visual analysis of design elements, as well as identifying the characteristics of Generation Z as consumers. The research method employs a qualitative descriptive approach through visual analysis. Data were collected through observations of three high-end local kids wear brand collections released between 2023 and 2025, visual documentation, and literature review on minimalist style and Generation Z consumer behavior. The analysis focuses on elements of color, silhouette, material, and pattern. The findings indicate that the dominance of earth-tone and neutral colors, oversized silhouettes, and the simplicity of forms and ornamentation represent the aesthetic preferences of Generation Z consumers. These findings suggest a shift in the character of kids wear from the dominance of bright and expressive colors toward a visually minimalist approach. This study contributes to the discourse on children's fashion design and consumer behavior within the context of contemporary visual culture in Indonesia.